A Statistically-Oriented Asymmetric Localization (SOAL) Model for Neuronal Outgrowth Patterning by Caenorhabditis elegans UNC-5 (UNC5) and UNC-40 (DCC) Netrin Receptors. Issue 1 (1st January 2018) - Limerick, Gerard; Tang, Xia; Lee, Won Suk; Mohamed, Ahmed; Al-Aamiri, Aseel; Wadsworth, William G
Abstract: Neurons extend processes that vary in number, length, and direction of "outgrowth". Extracellular cues help determine outgrowth patterns. In Caenorhabditis elegans, neurons respond to the extracellular UNC-6 (netrin) cue via UNC-40 (DCC) and UNC-5 (UNC5) receptors. Previously, we presented evidence that UNC-40 asymmetric localization at the plasma membrane is self-organizing, and that UNC-40 can localize and mediate outgrowth at randomly selected sites. Here, we provide further evidence for a statistically-oriented asymmetric localization (SOAL) model in which UNC-5 receptor activity affects patterns of axon outgrowth by regulating UNC-40 asymmetric localization. According to the SOAL model, the direction of outgrowth activity fluctuates across the membrane over time. Random walk modeling predicts that increasing the degree to which the direction of outgrowth fluctuates will decrease the outward displacement of the membrane. By differentially affecting the degree to which the direction of outgrowth activity fluctuates over time, extracellular cues can produce different rates of outgrowth along the surface and create patterns of "extension". Consistent with the SOAL model, we show that unc-5 mutations alter UNC-40 asymmetric localization, increase the degree to which the direction of outgrowth fluctuates, and reduce the extent of outgrowth in multiple directions relative to the source of UNC-6 . These results are inconsistent with current models, which predict that UNC-5 mediates a "repulsive" response to UNC-6 . Genetic interactions suggest that UNC-5 acts through the UNC-53 (NAV2) cytoplasmic protein to regulate UNC-40 asymmetric localization in response to both the UNC-6 and EGL-20 (Wnt) extracellular cues.